2022
DOI: 10.3390/children9081226
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Stewardship—The Impact of Rapid Diagnostic Testing for Paediatric Respiratory Presentations in the Emergency Setting: A Systematic Review

Abstract: Antimicrobial resistance is a growing public health crisis, propelled by inappropriate antibiotic prescription, in particular the over-prescription of antibiotics, prolonged duration of antibiotic therapy and the overuse of broad-spectrum antibiotics. The paediatric population, in particular, those presenting to emergency settings with respiratory symptoms, have been associated with a high rate of antibiotic prescription rates. Further research has now shown that many of these antibiotic prescriptions may have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…When comparing the rate of oseltamivir prescription for RMDTs versus standard tests, although the estimated odds ratio of 0.70 showed a reduction, the results were not statistically significant [ 43 ]. Weragama et al, 2022 [ 24 ] assessed, via an SLR, the clinical impact of rapid antigen and molecular diagnostic testing in children with respiratory symptoms presenting to ED. Although a formal MA was not conducted in the study, findings showed some evidence that antibiotic prescription and ancillary testing were reduced using RMDTs compared to other approaches, such as standard molecular test and immunofluorescence assay [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing the rate of oseltamivir prescription for RMDTs versus standard tests, although the estimated odds ratio of 0.70 showed a reduction, the results were not statistically significant [ 43 ]. Weragama et al, 2022 [ 24 ] assessed, via an SLR, the clinical impact of rapid antigen and molecular diagnostic testing in children with respiratory symptoms presenting to ED. Although a formal MA was not conducted in the study, findings showed some evidence that antibiotic prescription and ancillary testing were reduced using RMDTs compared to other approaches, such as standard molecular test and immunofluorescence assay [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weragama et al, 2022 [ 24 ] assessed, via an SLR, the clinical impact of rapid antigen and molecular diagnostic testing in children with respiratory symptoms presenting to ED. Although a formal MA was not conducted in the study, findings showed some evidence that antibiotic prescription and ancillary testing were reduced using RMDTs compared to other approaches, such as standard molecular test and immunofluorescence assay [ 24 ]. Lastly, Vos et al, 2019 [ 39 ] provided a qualitative summary of studies assessing the clinical impact of RMDTs for respiratory infections, which showed that turnaround times were significantly shorter with RMDTs compared with standard molecular tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rapid diagnostic testing for respiratory infections in the emergency setting has been shown to prevent unnecessary antibiotic prescriptions. [32] It is, therefore, prudent to examine all test use to identify potential areas where testing may confer benefit as well as areas where testing causes harms.…”
Section: Rank Order Of Practice Variability Of Specific Testsmentioning
confidence: 99%
“…Editorials and reviews have attempted to define the term [9,[15][16][17], and some have detailed the various stages where interventions may be applied in the pre-analytical, analytical and post-analytical phases [9]. However, publications, including systematic reviews [18], retrospective studies [19,20] and multi-centre validation of machine learning tools [21], have used the term without defining it. One collaborative study regarding paediatric blood cultures (BCs) defined diagnostic stewardship as "optimising the use of diagnostic tests to improve treatment decisions" [22].…”
Section: Introductionmentioning
confidence: 99%